Vote Value Disparity and Judicial Review in Japan - Tsuji, Yuichiro (Revista de Investigações Constitucionais, 2018)
In November 2015, the Japanese Supreme Court ruled that that there was disparity in the number of members in the House of Representatives following the general elections of December 2014. The plaintiff argued that the results of the 2014 elections for the House of Representatives were null and void. The value of the votes should be equal to the total number of voters, according to Articles 14 and 44 of the Japanese Constitution. The vote value disparity has created controversy through several cases since the Japanese Constitution was established.